Controlling Blood Pressure with Mindfulness and Self Management Techniques for Hypertension Patients - Amriati Mutmainna; Wa Mina La Isa (Sarana Ilmu Indonesia (salnesia), 2022)
A healthy diet and regular physical activity are key components in improving your lifestyle to maintain normal blood pressure. We wanted to evaluate the effect of mindfulness practice on lifestyle behavior in hypertension patients in Makassar, South Sulawesi. The research design used a quasi-experimental design with approached a one-group pre-post-test design. Based on the results of the study, it was found to decrease the average value of systolic blood pressure for subjekts after giving mindfulness and self-management techniques, from 151,90 mmHg to 147,10 mmHg. In the statistical test of the effect of giving mindfulness and self-management techniques, the p-value = 0,000. Meanwhile, in diastolic blood pressure, there was a decrease in the average blood pressure from 93,70 mmHg to 90,50 mmHg or 3,20 mmHg. While the statistical test obtained a value of p = 0,000. The conclusion, there is a significant effect of controlling mindfulness and self-management techniques on controlling diastolic blood pressure for hypertension patients in the Public Health Center, Makassar City.